Za groš greha ob milijonskem jubileju - Podlesnik, Blaž (Slavistična revija, 2014)
This article, on the two hundredth anniversary of Lermontov's birth, is devoted to the less canonical works of his poetic legacy - from the so-called junker period, during which Lermontov wrote numerous pornographic texts for his companions. Russian literary history has frequently tended to marginalize them as artistically insignificant. I explain them in the context of the entire poetic oeuvre as an example of a typical authorial attitude towards the predominant poetic languages of the time.
Keywords: 19.st.; junkersko obdobje; klasicizem; Lermontov, Mihail Jur'evič, 1814-1841; pornografija; realizem; romantizem; ruska književnost; ruska poezija; ruski pesniki; Russian literature